Long-term function after pseudo-pollicization of the little finger. (June 2014) - Medina, J. A.; Elliot, D.; Giesen, T.; Foucher, G.
This article presents a technique for facilitating use of pinch between the ring and little fingers for use in rare cases of congenital absence, or severe hypoplasia, of the thumb in which pollicization of the index finger is impossible, or not advised because the child is already pinching by scissor action between the ring and little fingers. The technique avoids drawing attention to the hand, as is the case after true pollicization of the little finger. The technique was used in five hands in five children. Three of the patients could only be followed for under 2 years. Two patients were available for longer follow-up of 6 years and 2 months and 3 years after surgery. The surgery was shown to facilitate opening of the web and pinch between the little and ring finger tips, and continues to be of functional value to the children as they grow.